Phytochemical, analgesic, antibacterial, and cytotoxic effects of Alpinia nigra (Gaertn.) Burtt leaf extract - A.M. Abu Ahmed; Farjana Sharmen; Adnan Mannan; Md Atiar Rahman (Journal of Traditional and Complementary Medicine, 2015)
This research evaluated the phytochemical contents as well as the analgesic, cytotoxic, and antimicrobial effects of the methanolic extract of Alpinia nigra leaf. Phytochemical analysis was carried out using established methods. The analgesic effects of the extract were measured with the formalin test and tail immersion test. The antibacterial activity of the extract was evaluated using the disc diffusion technique. Cytotoxicity was assessed with the brine shrimp lethality bioassay. Data were analyzed with one-way analysis of variance using statistical software (SPSS, Version 19.0). The qualitative phytochemical screening of A. nigra leaf extract showed the presence of medicinally active secondary metabolites such as alkaloids, glycosides, cardiac glycosides, flavonoids, steroids, tannins, anthraquinone glycosides, and saponins. The extract at a dose of 200 mg/kg revealed a prevailed central nociception increasing the reaction time in response to thermal stimulation. The extract also showed a response to chemical nociceptors, causing pain inhibition in the late phase. The leaf extract (2 mg/disc) showed mild antibacterial activity compared to tetracycline (50 μg/disc). In the brine shrimp lethality bioassay, the LC50 (lethal concentration 50) value of the extract was found to be 57.12 μg/mL, implying a promising cytotoxic effect. The results evidenced the moderate analgesic and antibacterial effects with pronounced cytotoxic capability.